Identificación plan de negocio: comercialización y exportación de cannabis medicinal a Toronto - Canadá (2020)
The cannabis plant has been used throughout history by many cultures, for its medicinal properties, although it is worth remembering that in some places it has been misused when used for recreational and illegal purposes, so that today some countries forbid it. We are in an era where every day advances in technology and research are seen, and even more so in medicine, this being a great advantage for the economic opening and development of the country, due to the ease of having crops and production and subsequent transformation of this plant. Canada is chosen as the destination to export for its stable economy, the elimination of tariff barriers for this type of product, for its customs efficiency and also that thanks to the free trade agreement many negotiations with this country can be carried out from now on and thus managing to increase the economic competitiveness of Colombia.